Determining and improving shared leadership in an elite junior volleyball team - van Kruijsbergen, M.; Pijpers, J. R.; Hutter, R. I. (The Sport Psychologist, 2020)
Shared leadership contributes to team functioning, collective efficacy, and team resilience. This applied study aimed to increase shared leadership by providing role clarification and tailored leadership interventions and to systematically evaluate the effects of these interventions. A leadership-intervention program was delivered with a female elite junior volleyball team of 20 players (age, M?=?15.14, SD?=?0.73). The intervention included acquaintance, recognition, analysis, and practice with leadership behavior during training/competition and was conducted before the start of the season. Changes in leadership were evaluated with a social-network analysis. Results showed that after role clarification, social- and external-leadership scores increased significantly. Task-, motivational-, and social-leadership scores improved significantly after the leadership-development intervention. The study offers a detailed description of the intervention and a systematic evaluation of results. Role clarification and a leadership program provide quick and practical avenue to increase awareness and shared leadership skills.